Stable-GARCH models for financial returns: Fast estimation and tests for stability - Marc S. Paolella (Econometrics, 2016)
A fast method for estimating the parameters of a stable-APARCH not requiring likelihood or iteration is proposed. Several powerful tests for the (asymmetric) stable Paretian distribution with tail index 1 < α < 2 are used for assessing the appropriateness of the stable assumption as the innovations process in stable-GARCH-type models for daily stock returns. Overall, there is strong evidence against the stable as the correct innovations assumption for all stocks and time periods, though for many stocks and windows of data, the stable hypothesis is not rejected.
Keywords: C12; 330; APARCH; asymmetric stable Paretian; Hill-type tail estimators; sum-stability